Narrowband perfect metasurface absorber based on impedance matching - Butt, Muhammad Ali; Kazansky, Nikolai Lvovich (Photonics Letters of Poland, 2020)
We presented a numerical investigation of a metamaterial narrowband perfect absorber conducted via a finite element method based on commercially available COMSOL software. The periodic array of silicon meta-atoms (MAs) are placed on 80 nm thick gold layer. The broadband light at normal incidence is blocked by the gold layer and silicon MAs are used to excite the surface plasmon by scattering light through it. Maximum absorption of 95.7 % is obtained at the resonance wavelength of 1137.5 nm due to the perfect impedance matching of the electric and magnetic dipoles. The absorption is insensitive to the wide-angle of incidence ranging from 0 to 80 degrees. We believe that the proposed metamaterial device can be utilized in solar photovoltaic and biochemical sensing applications. Full Text: PDF References Y. Cheng, X.S. Mao, C. Wu, L. Wu, R.Z. Gong, "Infrared non-planar plasmonic perfect absorber for enhanced sensitive refractive index sensing", Optical Materials, 53, 195-200 (2016). CrossRef S. S. Mirshafieyan, D.A. Gregory, "Electrically tunable perfect light absorbers as color filters and modulators", Scientific Reports,8, 2635 (2018). CrossRef D.M. Nguyen, D. Lee, J. Rho, "Control of light absorbance using plasmonic grating based perfect absorber at visible and near-infrared wavelengths", Scientific Reports, 7, 2611 (2017). CrossRef Y. Sun, Y. Ling, T. Liu, L. Huang, "Electro-optical switch based on continuous metasurface embedded in Si substrate", AIP Advances, 5, 117221 (2015). CrossRef H. Chu, Q. Li, B. Liu, J. Luo, S. Sun, Z. H. Hang, L. Zhou, Y. Lai, "A hybrid invisibility cloak based on integration of transparent metasurfaces and zero-index materials", Light: Science & Applications, 7, 50 (2018). CrossRef S. K. Patel, S. Charola, J. Parmar, M. Ladumor, "Broadband metasurface solar absorber in the visible and near-infrared region", Materials Research Express, 6, 086213 (2019). CrossRef Q. Qian, S. Ti, C. Wang, "All-dielectric ultra-thin metasurface angular filter", Optics Letters, 44, 3984 (2019). CrossRef P. Yu et al., "Broadband Metamaterial Absorbers", Advanced Optical Materials, 7, 1800995 (2019). CrossRef Y. J. Kim et al., "Flexible ultrathin metamaterial absorber for wide frequency band, based on conductive fibers", Science and Technology of advanced materials, 19, 711-717 (2018). CrossRef N.L. Kazanskiy, S.N. Khonina, M.A. Butt, "Plasmonic sensors based on Metal-insulator-metal waveguides for refractive index sensing applications: A brief review", Physica E, 117, 113798 (2020). CrossRef H. E. Nejad, A. Mir, A. Farmani, "Supersensitive and Tunable Nano-Biosensor for Cancer Detection", IEEE Sensors Journal, 19, 4874-4881 (2019). CrossRef